PERLINDUNGAN HUKUM BAGI PASIEN DALAM PELAYANAN KESEHATAN DI RUMAH SAKIT JIWA PROVINSI BALI - I MADE ARTANA; Kadek Ary Purnama Dewi; I Gede Mahatma Yogiswara W; I Dewa Made Adhi Hutama (Jurnal Yustitia, 2025)
In the legal aspect of health, the relationship between the patient and the doctor as a party has rights and obligations that must be respected. Patients will accept all actions that will be taken by doctors because they are considered to know and understand their health conditions with the aim of treatment or healing. Before the action is taken, it is necessary to have an agreement on the medical action to be carried out on the patient, which can be in the form of written or verbal consent. But in reality, if there is a loss to the patient due to health services, legal protection for patients related to medical services can be said to be still not optimal. Therefore, legal protection is needed for patients in health services at the Mental Hospital Bali Province. How is legal protection for patients in health services at the Bali Provincial Mental Hospital. How are efforts to resolve patient complaints in health services at the Mental Hospital Bali Province. Legal protection for patients in health services at the Mental Hospital Bali Province has been carried out in accordance with the laws and regulations regulated in health law sources which are quite broad and complex. The Mental Hospital Bali Province in carrying out or providing health services to patients has internal regulations that guide the hospital, namely Hospital By Laws which is used as a reference in operating hospitals. Efforts to resolve patient complaints in health services at the Mental Hospital Bali Province can be done in writing and orally. In the settlement of patient complaints, efforts are made to resolve them through the process of mediation and deliberation by involving the Complaint Handling Team, Deputy Director of Services and Director, and if needed in the mediation process, they will coordinate with other departments. As well as a form of compensation if the patient feels aggrieved while receiving health services at the Mental Hospital Bali Province.